2012
DOI: 10.4196/kjpp.2012.16.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Protects Spinal Cord Motoneurons Against Chronic Glutamate Excitotoxicity by Inhibiting Microglial Activation

Abstract: Glutamate excitotoxicity is emerging as a contributor to degeneration of spinal cord motoneurons in amyotrophic lateral sclerosis (ALS). Recently, we have reported that ghrelin protects motoneurons against chronic glutamate excitotoxicity through the activation of extracellular signal-regulated kinase 1/2 and phosphatidylinositol-3-kinase/Akt/glycogen synthase kinase-3β pathways. Previous studies suggest that activated microglia actively participate in the pathogenesis of ALS motoneuron degeneration. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Additionally recent reports showed that ghrelin protects spinal cord motor neurons against glutamate excitotoxicity (Lim et al, 2011;Lee et al, 2012c) and inhibits kainate-induced hippocampal neuronal cell death by inhibiting MMP-3 expression (Lee et al, 2010a). We also reported that BSCB disruption and hemorrhage, as well as apoptotic cell death are blocked, allowing the functional recovery to be improved by ghrelin treatment, which is mediated through GHS-R1a in rat SCI model (Lee et al, 2010b(Lee et al, , 2014b.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally recent reports showed that ghrelin protects spinal cord motor neurons against glutamate excitotoxicity (Lim et al, 2011;Lee et al, 2012c) and inhibits kainate-induced hippocampal neuronal cell death by inhibiting MMP-3 expression (Lee et al, 2010a). We also reported that BSCB disruption and hemorrhage, as well as apoptotic cell death are blocked, allowing the functional recovery to be improved by ghrelin treatment, which is mediated through GHS-R1a in rat SCI model (Lee et al, 2010b(Lee et al, , 2014b.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that ghrelin possesses neuroprotective effects in various models, some of which were dependent on the activity of the PI3K/Akt signaling pathway (Lee et al, 2012;Zhang et al, 2013). By activating the PI3K/Akt signaling pathway, ghrelin can alter the status of the Bcl-2 family of proteins, inhibit cytochrome c release and caspase-3 activity and promote the survival of neuronal cells (Hong et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Ghrelin, Unacylated Ghrelin, and Obestatin Secretion and Activity in Acute and Chronic Inflammatory States Several studies on the anti-inflammatory activity of ghrelin showed that only the acylated peptide was able to decrease the expression and production of proinflammatory cytokines: interleukin (IL)-1a, IL-1b, IL-6, and tumor necrosis factor (TNF)-a by activated T cells and by lipopolysaccharide (LPS)-activated monocytes and microglia (Dixit et al 2004;Li et al 2004;Theil et al 2009). Ghrelin has been shown to prevent also microglial activation in a mouse model of Parkinson's disease by inhibiting the expression of TNF-a and IL-1b induced by administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and to prevent the release of TNF-a and IL-1b from microglia treated with threohydroxyaspartate (Lee et al 2012;Moon et al 2009). Since GHS-R1a is not expressed in microglial cells, this effect of ghrelin on microglia activation might be either indirect or could be mediated by a yet unknown receptor.…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%